The role FinTech Start-ups play in the personal banking industry in South Africa - Nkosi, Doctor Teddy (My University, 2018)
The global financial crisis of 2008 became a platform for Financial Technology (FinTech). Investment in the sector has been growing substantially. Investment is largely driven by financial institutions who see that there is a real risk of them being disrupted. The failure of a number of such institutions across the globe was a turning point for FinTech start-up’s. What drives the FinTech disruption is not necessarily what product or service is offered but by who is offering that particular product or service. Due to its sound regulation, South Africa has avoided a great deal of the negative impact that banks across the globe have faced during the 2008 global financial crisis. The South African personal banking industry is largely dominated by five banks, namely ABSA, FNB (First National Bank), Standard Bank, Capitec and Nedbank. The researcher investigated the role FinTech Start-up’s play in the personal banking industry in South Africa. The research was focused on three areas within corporate entrepreneurship literature. Internal corporate venturing, external corporate venturing and collaboration A quantitative research method was employed to test the relationships. The first hypothesis looked at the positive relationship between personal banks and fintech start-ups in relation to external corporate venturing; the second explored the positive relationship between personal banks and fintech start-ups in relation to internal corporate venturing; and lastly, the third hypothesis examined the positive relationship between personal banks and fintech start-ups in relation to collaboration. Data was collected from individuals who were in management , mainly employed in the banking industry. The respondents were sent the questionnaire by email and a mobile link was provided for them to complete the questionnaire. Exploratory factor analysis was used to test validity of the constructs and all the constructs had a Kaiser-Meyer-Olkin value that is above 0.5. The Cronbach value of the constructs was above 0.7, thus demonstrating good reliability. The study found that no relationship exists between the personal banking industry and FinTech start-ups in relation to external corporate venturing, internal corporate venturing and collaboration. This suggests that the South African personal banking industry has not significantly sought to venture with FinTech start-ups internally or externally. This is also the case with collaboration. From a theoretical point of view the research has provided empirical evidence regarding corporate venturing in the South African personal banking space in relation to FinTech start-ups. The study therefore speaks to the need for South African banks to drive corporate entrepreneurial strategies for greater profitability, innovation and strategic renewal
Research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation Faculty of Commerce, Law and Management UNIVERSITY OF THE WITWATERSRAND BUSINESS SCHOOL
Keywords: Financial services industry$zSouth Africa; Banks and banking--Customer services--South Africa; Low-income consumers--South Africa; Microfinance--South Africa